Demographic and clinical determinants associated with intrauterine fetal mortality in the municipality of Pasto, 2010 - 2012 - Jurado Fajardo, Daniel; Chaves Marcillo, Melissa Catherine; Belalcázar Fajardo, Annyi Tatiana; Achicanoy Puchana, Denny Marcela; Guerrero, Carlos Andrés; Quiñonez Arteaga, Carmen Eugenia; Bravo Goyes, Luisa Mercedes (Universidad y Salud, 2017)
Introduction: Intrauterine fetal mortality (IUFM) is a public health problem because of its high rates worldwide and in low-and middle-income populations. However, it is a little-studied event and lacks visibility in public health policies, plans and programs. Objective: To analyze the sociodemographic and clinical determinants associated with IUFM in Pasto-Colombia. Materials and methods: A study, that includes 88 fetal deaths as cases and 88 live births as controls occurred in third level hospitals in Pasto-Colombia during 2010 and 2012, was carried out to determine the relationship between fetal mortality, clinical conditions (complications of pregnancy, gestational age, birth weight, prenatal controls, pathological and toxic medical history, or abortion) and sociodemographic conditions (age, ethnicity, occupation, marital status, stratum, area of residence , schooling, parity, displacement condition, planned pregnancy). Results: It was identified that the risk of fetal mortality is significantly lower with the increase in gestational age (OR ajustado = 0.76 IC95% 0.62; 0.93) and birth weight (OR ajustado = 0.99 IC95% 0.98; 0.99). Other clinical and sociodemographic variables were not associated. Conclusion: The results provide evidence for planning intervention plans that prioritize women whose fetus has a lower-than-normal weight and a risk of premature birth.